Implementasi Budaya Melayu Jambi Melalui Mata Kuliah Pengenalan Adat Melayu Jambi pada Mahasiswa PGSD Universitas Jambi - Alirmansyah Alirmansyah; Destrinelli Destrinelli; Vina Sandra Irani; Resti Karomah; Rosi Dwi Riski; Khairul Amri; Wuri Setianingtyas; Nindy Hafelia Putri; Bella Hendriyati (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to describe the implementation of Malay Malay Culture through the subject of introducing Malay Traditional Javanese culture to PGSD students at Jambi University. The research method used is descriptive qualitative using ethnographic type, because it will describe the characteristics of Jambi Malay culture within the scope of PGSD FKIP UNJA students. Data collection techniques using observation and interview techniques. Data analysis techniques were performed using interactive models (Miles and Huberman). Based on the results of the study, PGSD Unja students in the academic year 2019/2020 have been able to implement the culture of Malay Jambi very well through the introduction of Malay customary Javanese subjects. This is because, these students not only get theories during attending lectures, but also go directly to the field to find out the cultural background of the Malay Malay community, such as visiting the Siginjai Museum to find out the traditional tools used by the Malay Malay community in ancient times. As for the suggestions in this study, it is hoped that students can also apply the culture of Malay people to daily life so that they can further deepen the Malay Malay culture, and it is hoped that PGSD FKIP Unja students next academic year can also be preserving and preserving Jambi Malay culture